A novel mutation in the FGG gene causes hypofibrinogenemia in a Chinese family - Xiaoying Xie; Juan Du; Shunkang Geng; Baoqin Yi; Qingpu Li; Jiangcheng Zuo (Hereditas, 2024)
Abstract Congenital fibrinogen disorders are a group of coagulation deficiencies caused by fibrinogen defects and are divided into four types, including afibrinogenemia, hypofibrinogenemia, dysfibrinogenemia, and hypodysfibrinogenemia. In this study, we collected a family with hypofibrinogenemia, and genetics analysis identify a novel pathogenic variants (c.668G > C, p.Arg223Thr) in the FGG gene. And electron microscope observation revealed significant changes in the ultrastructure of fibrin of the proband. Our research expands the phenotypic and genetic spectrum associated with the FGG gene, which would facilitate in genetic counselling and prenatal genetic diagnosis.